Setting fisik graffiti tagging sebagai bentuk vandalisme di Kota Yogyakarta - Nino Ardhiansyah (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Physical settings graffiti tagging as vandalism in Yogyakarta The spatial identity of a city can be demonstrated through a clean, healthy, and organized city. A city that is clean, organized and free of vandalism is able to meet the city's identity standards. Uncontrolled vandalism perpetrators have increasingly tarnish the privilege of Yogyakarta as a city of education and culture. The act of graffiti tagging is done by writing the name of the gang/group on the media/building in public spaces using spray paint as a form of existence. Graffiti tagging will cause visual pollution that damages the privileges of the City of Yogyakarta. The phenomenon of the rise of graffiti tagging causes problems in the visualization of the representation of Yogyakarta City. The purpose of this study is to identify physical setting factors that influence the activity of graffiti tagging in Yogyakarta City and provide ideas through the preparation of Urban Design Guidelines related to graffiti tagging problems as a form of vandalism that occurs in Yogyakarta City. This study examines the physical settings and activities on the AM Sangaji corridor which is part of the imaginary axis of the city of Yogyakarta but often becomes the location of vandalism. Data collection is carried out through surveys and literature studies related to building functions, mass, height, color, transparency and setback. The identification results are then analyzed based on each element that is used as a research variable to find building criteria that tend to be objects of vandalism. The results of the study show that locations that are often used as graffiti tagging actions are the places that are located on the main road. The physical setting factors that most influenced the vandalism were lack of vegetation, small building mass, lack of transparency, and narrow setback dimensions. © 2020 Nino Ardhiansyah